Digital Oulipo: Programming Potential Literature. - Berkman, Natalie (DHQ: Digital Humanities Quarterly, 2017)
The formally constrained work of the Oulipo (l'Ouvroir de Littérature Potentielle, loosely translated as Workshop of Potential Literature) lends itself particularly well to digital studies, which was quickly recognized by the members of the group. To facilitate its goal of avoiding chance in its literary production, the group was naturally drawn to the determinism of computers, where true chance is simply impossible. In its early years, therefore, the group used algorithmic procedures as a starting point for various texts and also attempted to program these texts on actual computers, creating some of the first electronic literature and embarking on proto-digital humanities work as early as the 1960s and 1970s, later abandoning these efforts and relegating all subsequent activity to a subsidiary group. To understand the Oulipo's forays into computer science and more importantly, why they abandoned them, I designed and carried out one of the inaugural projects of the Princeton Center for Digital Humanities. The goal was twofold: first, through exploratory programming, I intended to create interactive, digital annexes to accompany my doctoral dissertation; more importantly, I hoped that by attempting to reproduce the Oulipo's own algorithmic efforts, I would gain similar insights into the nature of "Potential Literature" and be able to understand why the group abandoned such efforts after the 1970s. This article describes the content, development, and results of my project. For each of my three Python-based annexes, I offer a historical survey of the Oulipian text or procedure discussed within and the Oulipo's own proto-digital humanities experiments; then, I will talk about my own experiences as a coder-researcher, what learning Python has brought to my project, and how my exploratory programming offered me a new kind of critical reflection. Establishing these annexes forced me to learn to code, a type of work that does not only produce digital texts, but also helped me to reflect on the notion of chance in a more nuanced way. Finally, coding has allowed me to better understand the Oulipian mentality concerning this sort of digital experimentation.